How well-designed work makes us smarter : work that permits autonomy, demands problem-solving, and meets other criteria for good design can bolster employees' cognitive skills and ongoing learening - Parker, Sharon K.; Fisher, Gwenith G. (MIT Sloan Management Review, 2022)
Work that permits autonomy and problem-solving can bolster employees' cognitive skills and learning over time. While both fluid cognitive abilities and crystallized knowledge typically plateau or begin to decline with age, the authors' research finds that well-designed work can counter that effect. The authors discuss how organizations and managers can use good work design to strengthen their workforce's ability to adapt to new processes, tools, and roles.